2019
DOI: 10.1097/rlu.0000000000002821
|View full text |Cite
|
Sign up to set email alerts
|

18F-PSMA 1007 Uptake in Brain Metastases From Breast Cancer

Abstract: A 64-year-old woman with metastatic breast cancer on follow-up had suspicious recurrent brain metastases. She underwent 18F-FDG PET/CT, 18F-PSMA 1007 brain PET/CT, and brain MRI. 18F-PSMA 1007 showed intense tracer localization in the suspected recurrent brain metastasis in right parietal lobe and also picked up 2 more metastatic brain lesions, which had concurrent findings of metastasis in subsequent MRI. Our case highlights the feasibility of 18F-PSMA 1007 PET/CT imaging of brain metastases from nonprostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(81 citation statements)
references
References 12 publications
0
81
0
Order By: Relevance
“…Tissue staining with three different anti-PSMA antibodies showed heterogeneous results, with one antibody negative for all three tumor cell lines (ab58779, Abcam), one positive in all three (NBP1-45057, Novus), and one split (NBP1-89822, Novus). PSMAspecific binding was confirmed by application of the PSMA-antagonist PMPA which effectively suppressed 68 Ga-PSMA and 18 F-DCFPyL binding. They found that activated microglia expression (CD11b) was low intratumorally and peritumorally but activated astrocyte expression (GFAP) was high peritumorally.…”
Section: Expression Of Psma In Tissue and Preclinical Modelsmentioning
confidence: 89%
See 3 more Smart Citations
“…Tissue staining with three different anti-PSMA antibodies showed heterogeneous results, with one antibody negative for all three tumor cell lines (ab58779, Abcam), one positive in all three (NBP1-45057, Novus), and one split (NBP1-89822, Novus). PSMAspecific binding was confirmed by application of the PSMA-antagonist PMPA which effectively suppressed 68 Ga-PSMA and 18 F-DCFPyL binding. They found that activated microglia expression (CD11b) was low intratumorally and peritumorally but activated astrocyte expression (GFAP) was high peritumorally.…”
Section: Expression Of Psma In Tissue and Preclinical Modelsmentioning
confidence: 89%
“…They found that both PSMA-targeting tracers exhibited strong binding in the peritumoral area but moderate binding in the tumor core. In vivo animal PET imaging showed a higher tumor to background ratio (TBR) for 18 F-DCFPyL (TBR 6.28-7.92) than 68 Ga-PSMA (TBR 3.22-3.92). Tissue staining with three different anti-PSMA antibodies showed heterogeneous results, with one antibody negative for all three tumor cell lines (ab58779, Abcam), one positive in all three (NBP1-45057, Novus), and one split (NBP1-89822, Novus).…”
Section: Expression Of Psma In Tissue and Preclinical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other radiotracers have been used in clinical assessments of BM, such as sodium [ 18 F]fluoride (Na[ 18 F]F) to detect BM and study tumor responses after chemotherapy, 99 [ 18 F]-fluorocholine to detect BM and distinguish them from other brain tumors, 100 rubidium ( 82 Rb), 101 [ 68 Ga]Ga-PSMA-11, 102 and [ 18 F]-PSMA-1007 103 to detect BM, and [ 18 F]fluoromisonidazole ([ 18 F]FMISO) to study intra-tumoral hypoxia. 104 …”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%